2011
DOI: 10.1258/om.2011.110001
|View full text |Cite
|
Sign up to set email alerts
|

The management challenges of non-preeclampsia-related nephrotic syndrome in pregnancy

Abstract: Summary: Nephrotic syndrome in a pregnant woman may be challenging, especially when the onset is early in pregnancy or with severe manifestations. Preeclampsia is the most common cause of nephrotic syndrome in pregnancy; however, this review will focus on the management of other renal causes. The aim of this pragmatic review is to address clinical issues that clinicians looking after women with nephrotic syndrome may encounter during pregnancy and the postpartum period. First, we discuss some general issues re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
0
4
0
12
Order By: Relevance
“…47,48 Studies have suggested that nondihydropyridine calcium channel blockers such as diltiazem decrease proteinuria and thus diltiazem could be considered for women with hypertension and proteinuria during pregnancy, 49 though there are limited studies of this agent in pregnancy. 50,51…”
Section: Preconceptionmentioning
confidence: 99%
“…47,48 Studies have suggested that nondihydropyridine calcium channel blockers such as diltiazem decrease proteinuria and thus diltiazem could be considered for women with hypertension and proteinuria during pregnancy, 49 though there are limited studies of this agent in pregnancy. 50,51…”
Section: Preconceptionmentioning
confidence: 99%
“…Saat mendiagnosis sindroma nefrotik, perlu dinilai konsekuensi klinis yang menyertai hipoalbuminemia dan penurunan tekanan onkotik, seperti edema perifer, asites, dan efusi pleura/ perikardial. 4 Wanita dengan sindroma nefrotik biasanya memiliki edema. Akan tetapi, ini adalah tanda yang sangat nonspesifik selama kehamilan karena kemunculannya ditemukan pada dua pertiga kehamilan normal.…”
Section: Pembahasanunclassified
“…Beberapa pasien mungkin akan memerlukan diuretik harian, dengan dosis awal 5-10 mg. Loop diuretic seperti furosemid adalah yang paling sering dipilih sebagai duretik awal. 2,4 Monitoring ketat terhadap berat badan, elektrolit (natrium, kalium, kalsium, dan magnesium) dan bikarbonat (untuk menghindari alkalosis karena diuretik), keseimbangan cairan, dan tekanan darah mungkin diperlukan secara harian hingga TD stabil dan keseimbangan cairan dan elektrolit tercapai dengan diuretik. Serial fetal growth scan penting jika akan menggunakan diuretik pada kehamilan.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Nephrotic-range proteinuria complicates 0.32% of pregnancies, of which pre-eclampsia contributes to 0.19% 6,7. In women with LN where nephrotic-range proteinuria is a criterion for diagnosis, differentiating new-onset SLE or LN in pregnancy from pre-eclampsia remains a challenge.…”
mentioning
confidence: 99%